A qualitative study about palliative care patients’ experiences of comfort: implications for nursing diagnosis and interventions - Pinto, Sara (2021)
Background and objective:Comfort is a complex experience, particularly important to palliative care patients. Although it is listed in nursing classifications and taxonomies there is a gap between theory and practice. Thus, little research has been done about patient’s perceptions and experiences in this context of care. This paper aims to analyze palliative care patients’ experiences about comfort.Methods:Qualitative study with fifteen participants, using in-depth, semi-structured, face-to-face interviews, tape-recorded,transcribed verbatim and analyzed using interpretative content analysis.Results:Five main themes have been identified. Holistic comfort may be a difficult outcome for many end-of-life patients but the context of provision of care, the presence of family, the way information is managed, the search for meaning in life, and the need to keep life under control were perceived as important determinants for comfort.Conclusions:This study provides a general overview about comfort experiences and the main discomforts of hospitalized patients who are suffering from chronic and incurable diseases. Findings highlight comfort as a complex intervention within multidisciplinary palliative care team and this is supporting the nursing diagnosis “Impaired Comfort” as a syndrome. The study adds a contribution to the accuracy and completeness of nursing classifications and nursing practice in palliative care.